Effect of apolipoprotein E, A-I, A-IV, and lipoprotein lipase genotypes on fasting glucose, lipid, lipoprotein, and apolipoprotein levels, and their response to lifestyle intervention - Larson, Ilona; Justus Liebig University Giessen (My University, 1999)
Aims of the Study The first aim of this study was to investigate the effects of apolipoprotein (apo) E, A-I, A-IV, and lipoprotein lipase genotypes on various plasmaapolipoprotein levels as well as on serum total, low density lipoprotein (LDL) cholesterol, high density lipoprotein (HDL) cholesterol, triglyceride, and glucose values in 734 middle-aged and elderly female and male subjects. The second aim was to study the effect of a short-term lifestyle intervention program, including diet and exercise, on glucose and lipid response as well as the results of a long term follow-up. Methods Polymerase chain reaction (PCR) and restriction isotyping were used to examine the presence of restriction fragment length polymorphisms (RFLP´s) at the various gene loci. Results The allele frequencies for all polymorphisms investigated were similar to those reported in other studies for Caucasians. After adjustment for age, body-mass index, medications, alcohol use, and smoking, apo E genotype was noted to have significant effects on apo E, total cholesterol, LDL cholesterol, and glucose levels in females, and on apo E, LDL cholesterol, and HDL cholesterol levels, as well as on the total cholesterol (TC)/ HDL ratio in males. Female and male subjects with the apo E4 allele had significantly (p<0.05) lower plasma apo E (25 and 15%) and higher LDL cholesterol levels (5 and 2%), while those withthe apo E2 allele had significantly (p<0.05) higher apo E (32 and 27%) and lower LDL cholesterol levels (10 and 10%) than the apo E3/3 group. Moreover,female apo E4 carriers had significantly (p<0.05) lower glucose values (11%) than the apo E3/3 group. With regard to response, we observed for the firsttime, that the apo E genotype had a significant effect on glucose levels in males, with those carrying E2 allele having a greater response (-10.6%) compared to apo E3/3 (+0.8%) men, and those carrying the E4+ (-3.7%) allele. These data are consistent with the concept that, in addition to the well known effects of apo E genotype on LDL-C values, this locus plays a significant role in modulating plasma apo E levels and plasma glucose response to behavioral intervention. Concerning the apo A-I -75 bp polymorphism in the promoter region and +83 bp polymorphism in the first intron of the apo A-I gene, significant associationswere found for the -75 bp mutation in females only. Women carrying the rare A-allele had significantly (p<0.05) higher levels of apo B (5%), total (4%) andLDL cholesterol (6%), as well as a higher TC/HDL ratio (6%) compared to women carrying the G/G genotype. For the recently detected +83 bp mutation,we found a significant raising effect (p=0.002) of the rare M2- allele on apo A-I in men, and a weaker raising effect (p<0.05) on total cholesterol in men andwomen, respectively. Furthermore, a linkage disequilibrium (p=0.037) was found between the two polymorphisms. Males carrying the G/G M2+/- haplotypehad the highest apo A-I levels (p=0.021) compared to all the other haplotypes. Therefore, these data indicate an association between the -75 bp allele andfactors regulating LDL-C metabolism. However, no interactions between these apo A-I genotypes and HDL cholesterol levels, as well as lipid response to dietand exercise were observed. Concerning the apo A-IV 360 and 347 polymorphisms, no significant effects on any lipid traits were noted in females and males. However, in females, asignificant association (p=0.004) was observed with glucose levels, with women carrying the rare 2-allele having higher levels (11%) compared to the 1/1genotype. In response to lifestyle intervention, females with the apo A-IV 347 S/S genotype had significantly greater reduction in HDL-C (16.7%) versusfemales homozygous for the common T-allele (8.6%). These results indicate that the apo A-IV 360 and 347 mutations have some effect on lipid metabolism inthese subjects. The lipoprotein lipase Hind III genotype was noted to have a significant effect (p<0.05) on total and LDL cholesterol in women and on HDL cholesterol levels in men. Women being homozygous for the rare H- allele had significantly lower levels of total and LDL cholesterol (4% and 4%) than women being H+/+homozygotes. In men, those carrying the H- allele had significantly (p=0.003) higher HDL-C levels compared to the H+/+ genotype. However, with regard tothe lifestyle intervention, females heterozygous for the H- allele had significantly greater reductions in HDL-C (-9.0%) compared to females homozygous for the H+ allele (-5.6%). Therefore, this data suggest that in females, the rare H- allele has a cholesterol lowering, and therefore potentially cardioprotective effect, which seems to be offset by HDL cholesterol lowering during diet and exercise intervention. A long-term follow-up was carried out on a subset of 202 females and males who attended the program at two different occasions. The analysis of these datarevealed no long lasting effect of the short-term intervention program. When subjects returned to the Pritikin center after a mean time span of 1.7 years, theirbaseline lipid levels at visit 2 were similar or even slightly exceeded the levels at baseline 1. These data shows that it is difficult for free-living subjects toimplement and comply long-term with the intensive lifestyle changes carried out short term under carefully monitored conditions. Conclusion These results show that some of the candidate gene loci examined have a major impact on lipid and glucose levels, whereas others play a minor role.Concerning lipid lowering response to diet and exercise, the gene loci investigated were not significantly associated with individual variability in response in this particular experimental design. Our data shows that diet and exercise should remain the cornerstone for the reduction of CHD risk factors. The challenge is how to achieve long-term compliance to successful short-term intervention programs.
Keywords: ddc:570